LED light treatments enhance neuroprotective properties and differentially impact phenolic compounds and triterpenoid content in Gotu Kola (Centella asiatica (L.) Urb.) - Melissa Soun-udom; Maria Rita Garcia; Andreia P. Oliveira; Paula B. Andrade; Srunya Vajrodaya; Sutsawat Duangsrisai; Nelson G.M. Gomes (Current Plant Biology)
Due to an array of medicinal properties being attributed to Gotu kola (Centella asiatica (L.) Urb.), there is a growing demand for the incorporation of the plant as an herbal ingredient in drugs, cosmetics but mainly in dietary supplements and herbal drugs, which has been causing a gradual decline on its wild population. A possible way might be the improvement of the content in bioactive constituents that, in this specific matter, have been mainly labelled as being pentacyclic triterpenoids. We hypothesize that using light-emitting diode (LED) treatments can enhance its content in bioactives and improve its neuroprotective effects. Specific LED light treatments caused a metabolic shift, globally reducing the concentrations of the triterpenoids madecassoside, asiaticoside, and their corresponding aglycones. However, LED light treatments caused a pronounced increase in specific phenolic bioactives in comparison with samples obtained under sunlight, mostly pronounced in the concentrations of di-O-caffeoylquinic acids. Principal component analysis corroborated that the improvement on the neuroinflammatory status in BV-2 microglial cells and enhanced inhibition of tyrosinase are correlated with the increase in specific phenolic constituents resulting from LED light treatments. While the anti-neuroinflammatory effects in BV-2 microglial cells are demonstrated here for the first time, our core findings are mostly crucial for meeting the increased demand for C. asiatica in herbal products, as our LED light treatment boosts yields in specific phenolic bioactives and improves neuroprotective effects.